The Importance of Place of Residence on Hospitalized Outcomes for Severely Injured Trauma Patients: A Trauma Registry Analysis. Issue 3 (15th December 2019) - Heathcote, Katharine; Wullschleger, Martin; Gardiner, Ben; Morgan, Geoffrey; Barbagello, Holly; Sun, Jing
Abstract: Purpose: Socioecological factors are understudied in relation to trauma patients' outcomes. This study investigated the association of neighborhood socioeconomic disadvantage (SED) and remoteness of residence on acute length of hospital stay days (ALSD) and inpatient mortality. Methods: A retrospective cohort study was conducted on adults hospitalized for major trauma in a Level 1 trauma center in southeast Queensland from 2014 to 2017. Neighborhood SED and remoteness indices were linked to individual patient variables. Step‐wise multivariable negative binomial regression and proportional hazards regression analyses were undertaken, adjusting for injury and patient factors. Outcomes were ALSD and inpatient mortality. Findings: We analyzed 1, 025 patients. Statistically significant increased hazard of inpatient mortality was found for older age (HR 3.53, 95% CI: 1.77‐7.11), injury severity (HR 5.27, 95% CI: 2.78‐10.02), remoteness of injury location (HR 1.75, 95% CI: 1.06‐2.09), and mechanisms related to intentional self‐harm or assault (HR 2.72, 95% CI: 1.48‐5.03, ). Excess mortality risk was apparent for rural patients sustaining less severe injuries (HR 4.20, 95% CI: 1.35‐13.10). Increased risk for longer ALSD was evident for older age (RR 1.35, 95% CI: 1.07‐1.71), head injury (RR 1.39, 95% CI: 1.19‐1.62), extremity injuries (RR 1.82, 95% CI: 1.55‐2.14), and higher injury severity scores (ISS) (RR 1.51, 95%: CI: 1.29‐1.76). Conclusions: Severely injured rural trauma patients are more likely to be socioeconomically disadvantaged and sustain injuries predisposing them to worse hospital outcomes. Further research is needed to understand more about care pathways and factors influencing the severity, mechanism and clinical consequences of rural‐based traumatic injuries.